PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SENI RUPA KELAS VII SMPN 34 PADANG - FATIJAH, Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2019)
The research aimed to find out whether project based learning effects more in the students learning  arts outcome rather than conventional learning models which is seen from differences in learning   outcomes of students taught using Project Based Learning learning models with student learning  outcomes using conventional learning models. The research used quantitative research by having experiment method. The finding showed that students who used project based learning had higher  scores rather than who used conventional based learning.Kata kunci: Seni Budaya, Seni Rupa, Model Pembelajaran, Project BasedLearning, Hasil Belajar